2015
DOI: 10.1186/s12889-015-2608-2
|View full text |Cite
|
Sign up to set email alerts
|

Time trends and sex differences in associations between socioeconomic status indicators and overweight-obesity in Mexico (2006–2012)

Abstract: BackgroundAlthough the associations between specific socioeconomic status (SES) indicators and overweight or obesity (OWOB) have been studied in different countries, fewer evidence exists for these associations when multiple SES indicators are considered simultaneously. Furthermore, there are few studies investigating time trends in OWOB and their relation with SES in upper-middle income countries, especially for men. The present study contributes to a better understanding of the nature and evolution of the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 22 publications
5
18
0
1
Order By: Relevance
“…However, this association disappeared after adjusting for other SES indicators, showing the importance of considering other SES pathways for weight gain. This is consistent with the results reported by Quezada et al by using ENSANUT data for 2006 and 2012 (29). For women, the association between education and BMI has been previously described in Mexico (5,7,8,29), but nearly all studies failed to adjust for other SES indicators.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, this association disappeared after adjusting for other SES indicators, showing the importance of considering other SES pathways for weight gain. This is consistent with the results reported by Quezada et al by using ENSANUT data for 2006 and 2012 (29). For women, the association between education and BMI has been previously described in Mexico (5,7,8,29), but nearly all studies failed to adjust for other SES indicators.…”
Section: Discussionsupporting
confidence: 91%
“…The association for 2006 and 2012 was significant for middle and high assets; in 2016, the association held only for the high‐asset group. Studies using the National Health Survey of 2000 and ENSANUT of 2006 and 2012 showed similar associations for men , although other SES indicators, such as insurance coverage, participating in a cash‐transfer program, or ethnicity, were not considered as confounders. In women, assets were not associated with BMI in any of the survey years.…”
Section: Discussionmentioning
confidence: 92%
“…Nearly 90% of women in the MTC attended college, compared with the 15% of adults in Mexico who have attained tertiary education 32. Our findings of an inverse association of SEP and obesity in this study are consistent with reported associations among larger representative populations of women in the USA,33 Latin America34 and Mexico,35 where between 20% and 50% reductions in obesity risk were observed for women in the highest versus lowest category of education and other SEP indicators. Obesity was also more common among European women with less than primary education compared with those with tertiary education, with relative risks ranging from 1.75 to 6.78 6.…”
Section: Discussionsupporting
confidence: 91%
“…Sample size was estimated based on a statistical power of 80% with a 0.05 alpha value, and combined prevalence of normal-weight (29.5%) and hypomagnesemia (35%) [12,13]. The required sample size was of at least 125 individuals per group.…”
Section: Introductionmentioning
confidence: 99%